Cover Image, Volume 52, Issue 12. Issue 12 (15th June 2014) - Unknown
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> On page 1737 (DOI: 10.1002/pola.27175), Chang‐Feng Li, Qi‐Kai Zhang, Hai‐Jian Tian, Chun‐Peng Chai, Long‐Cheng Gao, Zhihao Shen, Xing‐He Fan, and Yun‐Jun Luo report the synthesis of polydimethylsiloxane‐based rod‐coil‐rod triblock copolymers using nitroxide mediated radical polymerization. SAXS and TEM results demonstrate that the triblock copolymers form lamellar structures. Upon heating, the blocks become liquid crystalline within the lamellar structures of the block copolymers, resulting in hierarchically ordered structures. These triblock copolymers are potentially useful as thermoplastic liquid crystal elastomers due to their distinctly different glass transition temperatures.